Industrial training report: Institut Pendidikan Guru Kampus Pendidikan Islam, Bangi / Athirah Dania Anuar - Anuar, Athirah Dania (Universiti Teknologi MARA, Negeri Sembilan, 2024)
The results of the reports that have been made are related to the industrial training that is mandatory for Diploma in Information Management students from the subject coded IMD310. Industrial training should be for eight weeks equivalent to 2 months. The purpose of this industrial training is to provide students with the experience of a real working atmosphere with what has been learned in class. The importance of this industrial training is very important to help in the selection of a career field to pursue and train yourself to face other challenges in the world of work.